Association of Dyslipidemia and Type-I Diabetes Mellitus Among Children Up to 16 Years of Age - Soobia Akhter, Zubair Khoso, Versha Rani Rai, Taj Muhammad Laghari, Roshia Parveen, Shazia Mahar, Mohsina Noor Ibrahim (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Diabetes is associated with a high risk of cardiovascular disease (CVD). Hypertriglyceridemia & low HDL-C values are the most common symptoms of diabetic dyslipidemia. Elevated LDL-C is a well-known CVD risk factor. Objective: To determine the association of dyslipidemia and type 1 diabetes mellitus among children up to 16 years of age. Material & Method Study design: Case-control study Settings: Outpatient department, National Institute of Child Health (NICH) Duration: Six months from 26th February 2018 to 28th August 2018 Data Collection procedure: All patients age 9 to16 years of either gender were included. Cases were defined as presence of fasting plasma glucose of > to 126.0 mg/dL (7.0 mmol/L) for more than one year whereas all patients with fasting plasma glucose of less than 126 mg/dL (7.0 mmol/L) were P a g e | 2 defined as controls. The blood sample was collected in a sterile manner after an overnight fasting of 8 hours and was sent to hospital laboratory and verified by pathologist. Results: Out of total 60 patients, the mean age of the patients was 11.23 ±1.76 years. Dyslipidemia was found to be significantly higher (n=26, 86.7%) among diabetic patients as compared to non-diabetic patients (n=18, 60%). (p-value 0.020) Moreover, the risk of dyslipidemia was 4.33 times higher among diabetic patients than that of non-diabetics (OR 4.33). Patients having >10 years of age and diabetes were 8.01 times more likely (OR 8.01, p-value 0.042) and diabetic males were 8.40 times more likely (OR 8.40, p-value 0.008) to have dyslipidemia. Conclusion: Highly significant association of dyslipidemia and type 1 diabetes mellitus was found among children up to 16 years of age.